EXPERIENCING THE PRESENT AND EXPLORING THE FUTURE WITH IMMERSIVE TECHNOLOGIES CASE STUDY: " ST. LAZARUS CHURCH PEDESTRIAN STREET", MACAU - Zhou RenWei (University of Saint Joseph, 2024)
In the present world, many cities have historical and culturally rich districts, but protectionism or economic reasons have slowed their development. Therefore, how to generate more value for these areas is crucial for a city with a deep and complex history. Using immersive virtual reality technology can help solve this problem, and this paper takes Macau's famous historical district as an entry point and starts from the perspective of the general public to explore and design some of the existing buildings and public areas in the district. The focus of this study is to explore the future development possibilities of historical and cultural districts in cities and experience the current situation of the district. Specifically, by studying the historical background and human investigation of ST. LAZARUS CHURCH PEDESTRIAN STREET (Chinese official name: 疯堂斜巷), the study uses immersive virtual reality technology to first create a scene of the existing building group in the district as a stage of protection for historical buildings. Then, it creates and presents a future building group scene in the district, which includes completed buildings and public area facilities after renovation and sustainable design. This renovation does not destroy the protected historical buildings at all, but is a protective exploration. The researchers used 3D computer graphics software (Blender) and virtual tour software (Kuula) to create the design, and users can freely explore the scene by ""walking"" virtually. The design includes two groups of architectural scenes of the ST. LAZARUS CHURCH PEDESTRIAN STREET in the present and the future. After entering the scene, users can freely switch between the present and the future time points to experience the different architectural scene atmospheres. Users can enter some buildings and public areas, and interact with objects in the scene to generate visual or auditory introductions to the target. Users can see the rough outline of the future historical and cultural district after the protective development in the free exploration of the virtual reality environment, which can inspire further public thinking about the development of historical and cultural street areas in the city. Users can explore and experience the project using professional virtual reality equipment or directly on the web. By using immersive virtual reality technology, the public can have a more intuitive and comprehensive understanding of the future development of historical and cultural street areas, and urban planners, professional architects, and clients of architectural design can all benefit from this technology, especially in the initial conceptual design and prototype design of buildings
Keywords: Conservation of historical building; Exploratory design; Reconstruction of historic district; Thesis and Dissertations Master of Design (MDG); University of Saint Joseph; Virtual reality technology

SenSwave: DRAW YOUR MUSIC BY EXPLORING THE RELATIONSHIP BETWEEN MUSIC, IMAGES, AND EMOTIONS - He, Minghao (University of Saint Joseph, 2024)
According to research, it is found that images, music, and emotions are closely related, and integrating visual and tactile elements into the music creation process, combined with auditory experience, can enhance emotional expression and understandability. The results highlight the potential of tangible interfaces in autonomous music creation and promoting emotional well-being. This work aims to explore the intersection of music creation, emotional expression, and technological innovation by creating a unique tangible interface for music. It does this by combining the challenges presented by the complexity of modern music production, the emotional issues faced by today's youth, and bringing a new way of expression to the phonograph technology. It hopes to draw inspiration from the historical significance of the phonograph through visual expression, user experience, and algorithmic music generation technology, and seek to provide a new way of music creation for young people who are creative and curious but not musicians, and provide a new way to express emotions. All things considered, the project demonstrates the feasibility and effectiveness of combining historical inspiration with modern technology to create innovative solutions for music technology. Furthermore, it is focusing on enhancing the interface design even more and carrying out longitudinal research to assess the long-term effects on emotional expressiveness and user experience. It is also being explored as an artistic installation, hoping to bring more changes and presentation methods and provide users with a more comprehensive and immersive music creation and emotional expression experience
Keywords: Artificial Intelligence; Interaction design; Interdisciplinary; Music generation; Tangible interface; Thesis and Dissertations Master of Design (MDG); University of Saint Joseph; Well-being Emotional expression

FLIIP: AN INTERACTIVE MULTIFUNCTIONAL TABLE DESIGN FOR PRESCHOOLERS - Tang, Qinghua (University of Saint Joseph, 2024)
With the rapid development of China's social economy, attention to children's education is also increasing. Among them, the preschool stage, the starting point of children's education, is the primary stage of children's cognitive, emotional, social, and motor skills development. At this critical time, providing children with an age-appropriate educational environment can significantly affect their personal growth, intellectual development, and emotional cultivation. Therefore, a multifunctional table that can meet the learning needs of preschool children and promote early cognitive development is essential. This work takes preschool children as the user object of our study to deeply explore the needs and obstacles of the target users. It summarizes the requirements and principles of children's furniture design based on children's physiological and psychological characteristics. A design scheme of an intelligent multifunctional preschool children's table is proposed based on ergonomics and digital technology. The objective through this work, is to create a preschool children's table that not only meets the learning needs of preschool children but also promote fun and can encourage the development of children's early cognitive ability
Keywords: Thesis and Dissertations Master of Design (MDG); University of Saint Joseph; children's furniture; interactive; multifunctional; preschool children; preschool children's table

Exploring Interactive Wearable: Enhancing Emotional Release and Expression in Modern Fashion Design - Zhai, Jingwen (University of Saint Joseph, 2024)
As technology evolves swiftly and consumers call for more customization, the study of interactive fashion design is increasingly emerging as a key topic within the fashion industry. The goal of this research is to investigate merging intelligent technology with apparel design, realizing functional enlargements and enriching the user experience by employing interactive design. Initially, this document examines key theories and ongoing studies in interaction design, intelligent textiles, and wearable tech, pinpointing the current research voids and difficulties. This section then presents a range of methodologies used in the study, encompassing literature review, case analysis, and interviews with experts, to thoroughly analyze and assess all facets of interactive apparel design. This document suggests a methodical design of interactive clothing, outlining the entire process from initial design to the creation of prototypes. The practicality and efficiency of the design methodology are proven by creating prototypes and conducting trials. Findings from the experiments indicate that interactive attire offers substantial benefits in terms of functionality, comfort, and user experience. The research offers both theoretical backing and pragmatic advice for designing interactive attire, while also highlighting paths for upcoming advancements in fashion technology. In conclusion, the document examines the shortcomings of the existing research and potential research paths, aiming to offer valuable guidance for advancing the development of clothing styling and wearable tech
Keywords: Fashion design; Thesis and Dissertations Master of Design (MDG); University of Saint Joseph; clothing interactive devices; emotion and perception; emotional user experience; interactive design

Park-meter: Designing an Innovative Macau System - Cheang, Chi Tat (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Design (MDG); University of Saint Joseph

Experience the Past in the Present with Immersive Technologies Case Study: “The Old Ladies’ House”, Albergue, Macau - Chang, Tin Lan (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Design (MDG); University of Saint Joseph

DEVISING THE IMPACT OF THE FEMALE PERSPECTIVE IN THE GAME DESIGN - Luo, Min (University of Saint Joseph, 2024)
Within the realm of video games, female characters often become ensnared in stereotypes, thus becoming objects of the male gaze. Moreover, the neglect of female characters' subjectivity in game design reflects a failure to acknowledge their agency. Additionally, the female perspective is frequently disregarded in game design. These issues have had adverse effects, leading to designs that are less hospitable to women, perpetuating misogyny, sexual harassment, and discrimination in online gaming, and further marginalizing women within the gaming industry. Integrating feminist principles into video game design has the potential to dismantle the cultural center of inequality within gaming culture and foster a more diverse and inclusive video game world, brimming with possibilities. This research investigates such phenomena through a blend of questionnaires and online interviews. Following data refinement and summarization, it explores the potential fusion of feminism and game design. While findings from these studies aid in establishing a framework for this synthesis, feminist game research presents complexity. The study offers pertinent references aimed at advancing the field
Keywords: Female Characters; Feminism; Game Design; Stereotypes; Thesis and Dissertations Master of Design (MDG); University of Saint Joseph; Video Games; Women

Assisting the Creative Processes in Visual Merchandising for Luxury Fashion Retail - Soares, Patricia Alexandra Ferreira (University of Saint Joseph, 2023)
This dissertation aims to research the need and viability of creating a digital platform that assists the creative processes naturally linked to Visual Merchandising. Through the proposal of a digital platform that works as a co-creative tool for display archives and a co-creative tool for display set-ups through mood boards, we will aim at improving the teamwork in retail and provide a unique, fast-forward platform for information sharing and input under the direction of Visual Departments. Building on rich source materials such as bibliography, scientific papers, news, and articles, and interviewing Visual Merchandisers actively working in the field, we will show the importance of creativity in Luxury Retail and what are the most common challenges in the field that we will propose a solution to. We will focus on the study of concepts, reviewing digital application tools being used by professionals and their best features and improvement opportunities. By gathering this information, we hope to provide accurate insights and information that proves the viability of this proposal and understand what features could serve best the target audience. Finally, we will present a conceptual idea in the form of sketches with functions of this digital application tool to be fully developed in the future and hopefully build a consistent well, designed commercial web-based application
Keywords: Luxury Retail; Thesis and Dissertations Master of Design (MDG); University of Saint Joseph; VM Digital Platform; VM Display Archives; VM Moodboard; Visual Merchandising